Cause marketing for dummies - Waters, Joe.; MacDonald, Joanna (Hoboken, NJ : Wiley, 2011)
Cause marketing benefits nonprofit and for-profit enterprises alike-- make it work for you! Discover how supporting a good cause provides a powerful competitive edge.
Includes index.
Keywords: Social marketing; Nonprofit organizations -- Marketing